Experience of Menopausal Symptoms and Perception of Menopause among Women at Bharatpur Chitwan Nepal: - Ranabhat, Mina Kumari; Thapa, Basanta; Neupane , Sarmila; Pokheral, Manju (Birat Journal of Health Sciences, 2025)
Introduction: Menopause is a natural biological process in women’s life which occurs commonly between the ages of 45-55 years worldwide. The mean age of  menopause was 48.02 years.Objectives:  The objective of the  study are to assess the experience of menopausal symptoms,level of perception of menopause and to find out the association between level of perception and selected variables.Methodology: A cross-sectional study design was conducted by using non probability  convenience sampling technique with structured interview schedule among 425 women between the age group 45 to 60 years  in Bharatpur, Chitwan. The collected data entered in IBM SPSS version 20 and  analyzed by descriptive and inferential statistics.Results: Out of 425 respondents, 57.4% respondents belong to the  age group more than 50 years. Among them, 67.7% of respondents became menopause with  the mean age 48.93 years and  standard deviation was 3.21. Most of the respondents experienced all types of  symptoms  vasomotor, physical, psycho-social and  sexual. Among these symptoms within vasomotor 58.6% has hot flashes, in physical 76.9% feeling lack of energy, in psycho-social 65.9% experience sleep disturbances and in sexual 60.7% change sexual desire. Only 32.5% of respondents shared their symptoms with family. In present study, 75.5% of respondents had positive attitude towards menopause.Conclusion:  Based on the findings of the study, it is concluded that every women suffer from menopausal symptoms but they could not share to their  family. Raising the awareness programme on menopausal symptoms in community level  that can be managed and prevented sufferings.